Phytochemical Profile and Antioxidant Activity of Juglans regia L. Green Husk Extracts from Tuyserkan Region, Iran - Seyyed Khalil HosseiniHashemi; Hadi Baseri; Jakia Jerin Mehjabin; Md. Khorshed Alam; Sayed Khosrow HossinAshrafi; Marjan Lotfi (BioResources, 2025)
Green husk is a byproduct of the walnut (Juglans regia L.) and could be a potential source of phytochemicals with important bioactivities. The extracts of J. regia L. green husk collected from the Tuyserkan region of Hamedan province were evaluated for their phytochemical profile and antioxidant activities. The chemical composition of crude extracts was analyzed by liquid chromatography-mass spectrometry (LC-MS) and gas chromatography-mass spectrometry (GC-MS). LC-MS analysis of green husk aqueous methanolic extract detected several compounds including phenolic acids, flavonoids, and hydrolyzable tannins. GC-MS analysis of the methanolic extracts revealed the presence of 1,2-dimethylbenzene (3.4%), methyl 14-methylpentadecanoate (2.82%), and methyl stearate (2.7%) as major compounds. The major components identified in the GC-MS analysis of non-polar hexane extract were (23S)-ethylcholest-5-en-3-β-ol (32.2%), δ-tocopherol (16.8%), lupeol (11.8%), and octadecane (5.7%). The antioxidant activity of the crude extracts was evaluated by DPPH assay, which showed aqueous methanol extract to be a more effective antioxidant agent (22.7%) compared to the hexane extract (14%) at the concentration of 1000 ppm. The findings suggest that methanolic extracts of walnut green husks from the Tuyserkan region are rich in bioactive compounds and exhibit more potent antioxidant activity than hexane extracts, demonstrating their potential use in pharmaceutical and food industries.